Information Security and Privacy Research 27th IFIP TC 11 Information Security and Privacy Conference, SEC 2012, Heraklion, Crete, Greece, June 4-6, 2012. Proceedings - Gritzalis, Dimitris; Furnell, Steven; Theoharidou, Marianthi; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
This book constitutes the refereed proceedings of the 27th IFIP TC 11 International Information Security Conference, SEC 2012, held in Heraklion, Crete, Greece, in June 2012. The 42 revised full papers presented together with 11 short papers were carefully reviewed and selected from 167 submissions. The papers are organized in topical sections on attacks and malicious code, security architectures, system security, access control, database security, privacy attitudes and properties, social networks and social engineering, applied cryptography, anonymity and trust, usable security, security and trust models, security economics, and authentication and delegation.
Keywords: Computer science; Computer Communication Networks; Data encryption (Computer science).; Computer software; Information Systems; Computer Science; Computer Communication Networks; Management of Computing and Information Systems; Data Encryption; Computers and Society; Algorithm Analysis and Problem Complexity; Information Systems Applications (incl. Internet).